Metal composite oxide and method for producing same
Patent Information
- Application Number
- JP2020110378
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-05
- Filing Date
- 2020-06-26
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-06-26
AI Technical Summary
【0027】 本発明によれば、Aサイト元素としてストロンチウム(Sr)を含み、Bサイト元素として金属元素(M)を含むペロブスカイト又はペロブスカイト類似の結晶構造を有する金属複合酸化物であっても、微細且つ異相の少ない化合物を得ることができる製造方法が提供される。
Smart Images

Figure 0007652379000001 
Figure 0007652379000002 
Figure 0007652379000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal composite oxide and a method for producing the same. [Background technology]
[0002] Many oxides having a perovskite or perovskite-like crystal structure have unique electrical or magnetic properties and are used in a variety of applications including electronic components. For example, the following documents disclose techniques related to perovskite oxides and / or oxides having a perovskite-like Rdolden-Popper oxide structure:
[0003] Patent Document 1 (JP 2009-263225 A) describes a compound having the general formula: (M 1 x1 M 2 X2 ) (m+1) (Ti (1-y-z) M 3 y M 4 z ) m O 3m+1-δ Compound (M 1 is alkaline earth metal, M 2 is rare earth metal, M 3 is a given transition metal, M 4 is a specific transition metal, rare earth metal, or base metal), and it is stated that the compound is known as a Rdolphin-Popper structure derived from perovskite and can be used as an electrode for an electrochemical device (claim 3,
[0040] and
[0048] of Patent Document 1).
[0004] Patent Document 2 (JP 2015-198065 A) discloses a metal-air secondary battery including a positive electrode having a Rudolf Denne-Popper type layered perovskite oxide and a solid electrolyte having a Rudolf Denne-Popper type layered perovskite oxide that has been subjected to a humidification reduction treatment, and describes that the reaction overvoltage at the positive electrode can be significantly reduced (Claims 1 to 5 and
[0012] of Patent Document 2).
[0005] Patent Document 3 (JP 2014-047307 A) discloses a photochromic material in which rare earth ions are contained in oxide crystals having a Rudolfden-Popper type perovskite structure, and describes that oxide crystals having a Rudolfden-Popper type perovskite structure are suitable for exhibiting a photochromic phenomenon (claims 1 to 5 and
[0014] of Patent Document 3). Furthermore, Patent Document 4 (JP 10-114570 A) discloses a method for producing a shape-anisotropic ceramic powder consisting of ceramic particles having a Rudolfden-Popper type layered perovskite structure, in which a ceramic raw material is heated in a melt or solution (claim 2 of Patent Document 4).
[0006] Thus, oxides having perovskite or perovskite-like crystal structures are used in various applications. Among these, oxides containing strontium (Sr) and transition metals (Me) in particular often exhibit catalytic functions. Catalysts are the core materials in clean energy technology. Therefore, perovskite or oxides having perovskite-like crystal structures containing strontium (Sr) and transition metals (Me) are expected to be used as catalytic materials that contribute to oxidation-reduction reactions (ORR) and oxygen evolution reactions (OER) in fields such as fuel cells, metal-air batteries, and water splitting.
[0007] The larger the surface area of a catalyst, the more active sites it has, and the better its catalytic performance. Therefore, it is desirable for the catalyst material to have a large specific surface area, i.e., to be fine. In order to achieve excellent catalytic performance, it is also desirable for the catalyst material to contain as few heterogeneous phases as possible.
[0008] Complex polymerization is a method widely used to synthesize metal oxide catalysts with large specific surface areas. In this method, a metal salt is dissolved in a glycol solution containing an oxycarboxylic acid such as citric acid to form a metal-oxycarboxylic acid complex. The solution is then heated to form a polymer gel through a dehydration esterification reaction. Finally, this gel is calcined and pyrolyzed to form a powder material. With this method, uniformity of the metal ions is achieved in the starting solution, and this uniformity is maintained in the polymer gel. As a result, it is said that the calcination temperature (pyrolysis temperature) can be lowered, and a fine, uniform powder material can be obtained.
[0009] An example of a document disclosing such a technique is Patent Document 5 (JP Patent Publication 2009-214033 A). Patent Document 5 describes a compound having the general formula: ALa4Ti4O 15 Regarding a photocatalyst having a structure in which a co-catalyst is supported on the surface of a catalyst substance made of a layered perovskite compound represented by the formula (I), it is described that a catalyst substance made of a layered perovskite compound can be obtained by a complex polymerization method, in which a raw material corresponding to the layered perovskite compound to be synthesized is mixed with a solvent such as ethanol, and then heated to react, and the resulting reaction product (catalyst substance precursor) is calcined (claims 1 to 5 and
[0025] of Patent Document 5). [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2009-263225 A [Patent Document 2] JP 2015-198065 A [Patent Document 3] JP 2014-047307 A [Patent Document 4] Japanese Patent Application Publication No. 10-114570 [Patent Document 5] JP 2009-214033 A Summary of the Invention [Problem to be solved by the invention]
[0011] Perovskite or oxides with a perovskite-like crystal structure containing strontium (Sr) and transition metals (Me) are expected to be useful as catalytic materials. In addition, complex polymerization is often used to synthesize metal oxide catalysts. However, when a metal oxide contains a cation with a large ionic radius such as strontium (Sr), it is difficult to synthesize a compound with a uniform composition even by the complex polymerization method. This is because it is difficult to maintain a complex containing a cation with a large ionic radius stably for a long period of time. As a result, the cation precipitates during the drying of the solvent, compromising the uniformity of the composition.
[0012] In particular, when the purpose is to synthesize a Rdolsden-Popper type compound, which has a crystal structure similar to perovskite, even a slight deviation in composition will result in the generation of a compound with different crystal symmetry and crystal structure. Therefore, it is difficult to synthesize a single-phase Rdolsden-Popper type compound by pyrolyzing the gel while maintaining a uniform state at the atomic level. On the other hand, in order to homogenize the composition, it is possible to pyrolyze the gel using a complex polymerization method to form a compound, and then repeatedly crush and sinter. However, when the complex polymerization method is used, a fine single-phase compound cannot be obtained even if the crushing and sintering are repeated.
[0013] The present inventors have conducted extensive research into the synthesis of a metal composite oxide having a perovskite or a perovskite-like crystal structure containing strontium (Sr) as an A-site element and a metal element (M) as a B-site element. As a result, they have discovered that a compound that is fine and has few heterogeneous phases can be synthesized by freezing and solidifying a raw material solution containing components of a metal composite oxide and a solvent to form a solidified material, sublimating the solvent while this solidified material is in a frozen state to form a metal salt mixture, and heating the resulting metal salt mixture, thereby completing the present invention.
[0014] Therefore, an object of the present invention is to provide a production method capable of obtaining a fine and less heterogeneous compound even when the metal composite oxide has a perovskite or perovskite-like crystal structure containing strontium (Sr) as the A-site element and a metal (M) as the B-site element. **Means for Solving the Problems**
[0015] The present invention includes the following aspects (1) to (11). In this specification, the expression "~" includes the numerical values at both ends thereof, that is, "X~Y" is synonymous with "X or more and Y or less".
[0016] (1) A method for producing a metal composite oxide having a perovskite or perovskite-like crystal structure containing strontium (Sr) as the A-site element and a metal element (M) as the B-site element, comprising the following steps: A step of preparing a raw material solution containing the constituent components of the metal composite oxide and a solvent, A step of freezing and solidifying the raw material solution, and sublimating and removing the solvent while keeping the obtained solidified product in a frozen state to obtain a metal salt mixture, and A step of heating the metal salt mixture to obtain a metal composite oxide, A method comprising the above steps.
[0017] (2) The method according to (1) above, wherein the metal composite oxide is a Ruddlesden-Popper type compound represented by the general formula: A n+1 B n O 3n+1 (where 0 < n ≦ 4).
[0018] (3) The method according to (1) or (2) above, wherein the metal element (M) is at least one selected from the group consisting of titanium (Ti), zirconium (Zr), iron (Fe), copper (Cu), manganese (Mn), cobalt (Co), nickel (Ni), niobium (Nb), tantalum (Ta), tin (Sn), ruthenium (Ru), iridium (Ir), rhodium (Rh), chromium (Cr), hafnium (Hf), aluminum (Al), and magnesium (Mg).
[0019] (4) The method according to (1) above, wherein the metal composite oxide is a Rudolfden-Popper type compound containing strontium (Sr) and a rare earth metal (Re) as A-site elements and a metal element (M) as a B-site element.
[0020] (5) The metal composite oxide is represented by the general formula Re 2-x Sr x MO 4±δ (wherein 0.5≦x≦1.5, 0≦δ≦0.25).
[0021] (6) The method according to (4) or (5) above, wherein the rare earth metal (Re) is one or more selected from the group consisting of lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), yttrium (Y) and erbium (Er).
[0022] (7) The method according to any one of (4) to (6) above, wherein the metal element (M) is one or more selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), iron (Fe), titanium (Ti), zirconium (Zr), hafnium (Hf), niobium (Nb), tantalum (Ta), tin (Sn), ruthenium (Ru), iridium (Ir), rhodium (Rh), chromium (Cr) and copper (Cu).
[0023] (8) The metal composite oxide has a BET specific surface area of 0.4 m 2 The method according to any one of (4) to (7), wherein the powder is a powder having a molecular weight of 1 / g or more.
[0024] (9) The method according to any one of the above (1) to (8), wherein the raw material solution is an aqueous solution of one or more kinds selected from the group consisting of nitrates, acetates, chlorides and sulfates of the constituents.
[0025] (10) Any of the above methods (1) to (9), wherein the raw material solution does not contain organic matter.
[0026] (11)A site element contains strontium (Sr), and B site element contains a metal element (M). It is a metal composite oxide having a perovskite or perovskite-like crystal structure, wherein the metal composite oxide has a general formula: A n+1 B n O 3n+1 (where 0 < n ≤ 4), and is a Ruddlesden-Popper type compound represented by, wherein the metal element (M) is one or more selected from the group consisting of titanium (Ti), zirconium (Zr), iron (Fe), copper (Cu), manganese (Mn), cobalt (Co), nickel (Ni), niobium (Nb), tantalum (Ta), tin (Sn), ruthenium (Ru), iridium (Ir), rhodium (Rh), chromium (Cr), hafnium (Hf), aluminum (Al) and magnesium (Mg); wherein the metal composite oxide is a powder having a BET specific surface area of 2.0 m 2 / g or more. Metal composite oxide.
Effect of the Invention
[0027] According to the present invention, there is provided a manufacturing method capable of obtaining a fine and less heterogeneous compound even for a metal composite oxide having a perovskite or perovskite-like crystal structure containing strontium (Sr) as an A site element and a metal element (M) as a B site element.
Brief Description of the Drawings
[0028] [Figure 1] Shows the X-ray diffraction pattern of the example sample. [Diagram 2] Shows the SEM image and composition surface analysis results of the example sample. [Diagram 3] Shows the linear sweep voltammogram of the example sample. [Figure 4] Shows the X-ray diffraction pattern of the comparative example sample. [Diagram 5] Shows the SEM image and composition surface analysis results of the comparative example sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Method for producing metal composite oxide In the method for producing a metal composite oxide of the present invention, the metal composite oxide contains strontium (Sr) as an A-site element and a metal element (M) as a B-site element. The metal composite oxide has a perovskite or a crystal structure similar to that of a perovskite. Perovskite is an oxide containing an A-site element and a B-site element and having a crystal structure represented by the general formula: ABO3. The crystal structure similar to that of a perovskite refers to a double-perovskite, Ruddlesden-Popper and / or Dion-Jacobson type structure.
[0030] The method for producing a metal composite oxide of the present invention includes the following steps: a step of preparing a raw solution containing components of the metal composite oxide and a solvent (raw solution preparation step), a step of freezing and solidifying the raw solution, and sublimating and removing the solvent from the resulting solidified product while it is still frozen to obtain a metal salt mixture (freeze-drying step), and a step of heating the metal salt mixture to obtain a metal composite oxide (calcination step). Each step will be described in detail below.
[0031] <Raw material solution preparation process> In the raw solution preparation step, a raw solution containing the constituent components (A-site elements and B-site elements) of the metal composite oxide is prepared. The raw solution is a solution in which the inorganic acid salts of the constituent components are dissolved in a solvent. In this respect, the raw solution is clearly distinguished from a slurry or suspension in which solid components are suspended. The inorganic acid salt is preferably one or more selected from the group consisting of nitrates, acetates, chlorides, and sulfates. Furthermore, the solvent may be selected from those having a melting point of around 0°C and a high vapor pressure. Examples of such solvents include water, cyclohexane, butanol, and the like. However, water is preferred because it is easy to handle. Therefore, the raw solution is preferably an aqueous solution of one or more selected from the group consisting of nitrates, acetates, chlorides, and sulfates of the constituent components. Such a raw solution may be prepared by a known method. For example, the raw solution may be prepared by dissolving the inorganic acid salts of the constituent components, such as nitrates, in a solvent such as water. Alternatively, the raw solution may be prepared by dissolving the metal, oxide, or hydroxide of the constituent components in an inorganic acid such as nitric acid.
[0032] It is preferable that the raw material solution does not contain organic matter. When synthesizing a compound by the complex polymerization method, an oxycarboxylic acid such as citric acid is added to an aqueous solution of a metal salt to prepare an oxycarboxylic acid complex, which is then heated and dried to form a complex gel. Alternatively, a glycol such as ethylene glycol is dissolved in a solution of a metal citrate complex to form a polymer gel. In any case, in the complex polymerization method, an organic matter (polymer) is contained in the gel, and this organic matter needs to be thermally decomposed. Therefore, if a metal that is likely to form a carbonate is contained in the constituent metals, undesirable carbonates are likely to be formed during thermal decomposition. In contrast, in the manufacturing method of the present invention, it is not necessary to add organic matter such as oxycarboxylic acid or glycol to the raw material solution. Therefore, carbonates are unlikely to be formed, and high-temperature heat treatment to thermally decompose them is not required.
[0033] <Lyophilization process> In the freeze-drying process, the raw solution is frozen and solidified, and the solvent is sublimated and removed from the resulting solidified material while it is still frozen, forming a metal salt mixture. By freezing and solidifying the raw solution, even if a raw solution containing strontium (Sr), which has a large ionic radius, is used, all metal ions are frozen and solidified while maintaining a uniform state in the form of metal salts in the solution. This makes it possible to make the distribution of metal ions in the resulting solidified material uniform at the atomic level.
[0034] The freezing and solidifying may be performed by cooling the raw material solution to its freezing temperature. The cooling temperature may be determined according to the component composition of the raw material solution, and is not generally limited. For example, when the raw material solution is an aqueous solution, the raw material solution may be brought into contact with or poured into a refrigerant at -10°C or lower. In this case, it is preferable to perform freezing rapidly, since the distribution of metal ions in the solidified product becomes more uniform. Therefore, it is preferable to rapidly cool the raw material solution. As a rapid cooling method, for example, liquid nitrogen at -196°C is used as a refrigerant, and the raw material solution is brought into contact with or poured into this liquid nitrogen. It is also effective to make the raw material solution into fine droplets and spray it into a refrigerant such as liquid nitrogen. By making the raw material solution into fine droplets, the raw material solution is instantly frozen. The liquid nitrogen can be removed by evaporating it after freezing and solidifying.
[0035] Next, the solvent is removed by sublimation while the solidified material is in a frozen state, to obtain a metal salt mixture. The form of the obtained metal salt mixture is not particularly limited, but may be, for example, a powder. In the frozen solidified material, metal ions are uniformly distributed. Therefore, by removing the solvent by sublimation while the solidified material is in that state, the metal ions maintain a uniform distribution state even in the metal salt mixture after the solvent is removed. In contrast, when the raw material solution is heated and dried to evaporate and remove the solvent, the metal components segregate in the dried material due to differences in the solubility of the metal components, and a uniform metal salt mixture cannot be obtained.
[0036] Sublimation of the solvent is carried out under reduced pressure. The lower the atmospheric pressure, the higher the sublimation rate. The atmospheric pressure is preferably 1 kPa or less, more preferably 100 Pa or less, and even more preferably 50 Pa or less. The higher the atmospheric temperature, the higher the sublimation rate. Therefore, the higher the atmospheric temperature, the more preferable it is within the range in which the solidified material maintains its frozen state. However, if the solidified material melts, it becomes necessary to dry the solvent, which impairs the uniform distribution of the metal ions. Therefore, when the solvent is removed by sublimation, it is necessary to maintain the solidified material in a frozen state.
[0037] <Firing process> In the calcination process, the metal salt mixture is heated to form a compound. Heating causes the decomposition of the metal salts and also causes reactions between the constituent components to form a compound. The metal ions contained in the metal salt mixture are uniformly distributed. Therefore, by using such a metal salt mixture, it is possible to synthesize a compound at a low temperature. As a result, grain growth can be suppressed, and a fine compound with few heterogeneous phases can be obtained. In contrast, in the metal salt mixture obtained by heating and drying the raw material solution, the metal components are segregated. Therefore, in order to obtain a single-phase compound, the synthesis temperature must be high, and a fine compound cannot be obtained.
[0038] The heating temperature in the calcination step may be determined according to the type of raw material or the target compound, and is not limited in general. However, the heating temperature is preferably 500 to 1500°C, more preferably 700 to 1300°C. The atmosphere during heating is not limited as long as the desired compound is obtained. However, an oxygen-containing atmosphere such as an oxygen atmosphere or an air atmosphere is preferable. By heating in an oxygen-containing atmosphere, it is possible to prevent the resulting compound (metal composite oxide) from being excessively reduced. In addition, heating in the calcination step may be performed multiple times. For example, the metal salt mixture may be calcined to obtain a calcined product, and the resulting calcined product may be calcined. In this case, the calcined product may be pulverized, and the pulverized calcined product may be calcined. By performing calcination and calcination in this way, or by inserting a pulverization step, the synthesis of the compound can be further promoted.
[0039] According to the manufacturing method of the present invention, it is possible to obtain a fine compound with few heterophases, even if it is a metal composite oxide having a perovskite or perovskite-like crystal structure containing strontium (Sr) as an A-site element and a metal element (M) as a B-site element. This compound can be used for various purposes including catalysis, and is particularly useful as a material for oxygen reduction catalysts and / or oxygen reaction catalysts.
[0040] Metal Complex Oxides The metal composite oxide of the present invention contains strontium (Sr) as an A-site element and a metal element (M) as a B-site element, and has a perovskite or perovskite-like crystal structure. Here, perovskite is an oxide containing an A-site element and a B-site element and having a crystal structure represented by the general formula: ABO3. The perovskite-like crystal structure refers to a double-perovskite, Ruddlesden-Popper, and / or Dion-Jacobson type structure. Here, double-perovskite is a crystal structure represented by the general formula: A2BB'O6, and Ruddlesden-Popper is a crystal structure represented by the general formula: A n+1 B n O 3n+1 The crystal structure is represented by the general formula: A'A n-1 B n O 3n+1 The compounds having these crystal structures have a similar crystal structure to perovskite and exhibit similar properties to perovskite compounds.
[0041] The metal composite oxide is preferably represented by the general formula: A n+1 B n O 3n+1It is a compound having a Rudorff-Dopper type crystal structure represented by (where 0 < n ≤ 4) (Rudorff-Dopper type compound). The Rudorff-Dopper type crystal structure is a kind of layered perovskite type structure and has a structure in which [ABO3] layers and [AO] layers are alternately stacked. As can be seen from this, the Rudorff-Dopper type compound has a crystal structure similar to that of a perovskite compound (ABO3), and therefore has various properties such as giant magnetoresistance, superconductivity, ferroelectricity, and catalytic activity.
[0042] In addition, in the above general formula, as long as the desired crystal structure can be obtained, fluctuations in the composition are allowed. For example, in the general formula ABO3 of perovskite, the ratio of A to B does not necessarily have to be exactly "1:1", and as long as it shows a perovskite type crystal structure, a deviation in the ratio is allowed. Also, depending on the valence of the ions in the crystal structure, lattice defects such as oxygen vacancies may exist, and in that case, the amount of oxygen (O) in the general formula may deviate.
[0043] The metal composite oxide of the present invention contains strontium (Sr) and a metal element (M) other than strontium (Sr) as constituent components. That is, strontium (Sr) occupies the A site of the crystal structure, and the metal element (M) occupies the B site. The metal element (M) may be a transition metal (Me). The metal element (M) is preferably at least one selected from the group consisting of titanium (Ti), zirconium (Zr), iron (Fe), copper (Cu), manganese (Mn), cobalt (Co), nickel (Ni), niobium (Nb), tantalum (Ta), tin (Sn), ruthenium (Ru), iridium (Ir), rhodium (Rh), chromium (Cr), hafnium (Hf), aluminum (Al), and magnesium (Mg).
[0044] As long as the perovskite or perovskite-like crystal structure is maintained, the A site may contain other components (ions) other than strontium (Sr). For example, a portion of strontium (Sr) may be replaced with other alkaline earth metal cations such as barium (Ba) or calcium (Ca) that are divalent. However, the proportion of strontium (Sr) occupying the A site is preferably 50 atomic % or more, more preferably 75 atomic % or more, and even more preferably 90 atomic % or more. The A site may be occupied only by strontium (Sr). In addition, oxygen ions (O 2- ) are converted to other anions such as chlorine and fluorine (Cl - , F - etc.) may be substituted.
[0045] The metal double oxide may be a Ruddlesden-Popper type compound containing strontium (Sr) and a rare earth metal (Re) as A-site elements and a metal element (M) as a B-site element. Here, rare earth metal (Re) is a general term for elements ranging from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71 in the periodic table, plus scandium (Sc) with atomic number 21 and yttrium (Y) with atomic number 39. Thus, the Ruddlesden-Popper type compound containing strontium (Sr), a rare earth metal (Re) and a metal element (M) exhibits various functions including a catalytic function.
[0046] This metal composite oxide has the general formula Re 2-x Sr x MO 4±δ(wherein 0.5≦x≦1.5, 0≦δ≦0.25). Here, the rare earth metal (Re) is preferably one or more selected from the group consisting of lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), yttrium (Y), and erbium (Er). The metal element (M) is preferably at least one selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), iron (Fe), titanium (Ti), zirconium (Zr), hafnium (Hf), niobium (Nb), tantalum (Ta), tin (Sn), ruthenium (Ru), iridium (Ir), rhodium (Rh), chromium (Cr) and copper (Cu). The metal element (M) may be a transition metal (Me). Here, the transition metal (Me) is a general term for elements present between the third group element and the eleventh group element in the periodic table. In addition, in the above general formula, as long as a desired crystal structure is obtained, fluctuations in the composition are allowed. For example, the ratio of the total molar amount of strontium and rare earth metals to the molar amount of the metal element (Sr+Re:M) does not need to be strictly "2:1", and deviations in the ratio are allowed as long as the Rdolphin-Popper type crystal structure is exhibited.
[0047] The metal composite oxide preferably has a BET specific surface area of 0.4 m 2 / g or more, and more preferably, the BET specific surface area is 2.0 m 2 / g or more. There is no particular upper limit to the BET specific surface area. However, it is typically 10.0 m 2is below / g. After synthesizing the metal composite oxide, performing ultrafine pulverization treatment is also effective in increasing the specific surface area without newly generating heterogeneous phases. For the ultrafine pulverization treatment, wet media stirring type pulverizers such as bead mills and attritors, and mechanical pulverization such as planetary mills and ball mills are effective, but not limited thereto. Further, when stress strain occurs in the oxide particles due to the ultrafine pulverization treatment, the stress strain can be removed by heat treatment at a temperature at which sintering between the particles does not occur. The heat treatment temperature at which sintering between the particles does not occur depends on the substance, but is generally 400 to 800 °C.
[0048] Further, the heterogeneous phase content of the metal composite oxide is preferably 10% by mass or less, more preferably 5% by mass or less, and still more preferably 1% by mass or less. The heterogeneous phase content may be 0% by mass, that is, a single phase. Thus, by using a metal composite oxide having a high specific surface area and a low heterogeneous phase content, various functions such as catalytic performance can be made excellent.
[0049] As an example of the metal composite oxide, it contains strontium (Sr) as the A-site element and a metal element (M) as the B-site element, has a perovskite or perovskite-like crystal structure, and the general formula: A n+1 B n O 3n+1 (where 0 < n ≤ 4), which is a Ruddlesden-Popper type compound, and the metal element (M) is one or more selected from the group consisting of titanium (Ti), zirconium (Zr), iron (Fe), copper (Cu), manganese (Mn), cobalt (Co), nickel (Ni), niobium (Nb), tantalum (Ta), tin (Sn), ruthenium (Ru), iridium (Ir), rhodium (Rh), chromium (Cr), hafnium (Hf), aluminum (Al), and magnesium (Mg), and an oxide that is a powder with a BET specific surface area of 2.0 m 2 / g or more is mentioned.
[0050] Thus, according to the present invention, even if a compound (metal composite oxide) having a perovskite or a perovskite-like crystal structure containing strontium (Sr) as an A-site element and a metal element (M) as a B-site element is obtained in a fine state with few heterogeneous phases. In particular, the present invention is useful for synthesizing Rudersden-Popper type compounds and compounds containing metals that easily form carbonates. Such compounds can be used in various applications including catalysis, and are particularly useful as materials for oxygen reduction catalysts and / or oxygen reaction catalysts.
[0051] In contrast, according to conventional methods, it was difficult to prepare a perovskite or a compound having a perovskite-like crystal structure containing strontium (Sr), which has a large ionic radius, in a fine state with few heterophases. In particular, when a Rudersden-Popper type compound is synthesized, compounds with different crystal symmetries and crystal structures are easily generated, and therefore it was difficult to prepare a single-phase compound. In addition, when a compound contains a metal that easily forms carbonates, such as lanthanum (La), it was difficult to prepare such a compound in a fine state with few heterophases. This is because carbonates are generated during synthesis, and high-temperature heat treatment is required to decompose the carbonates. EXAMPLES
[0052] The present invention is further illustrated by the following examples.
[0053] Example 1 (1) Preparation of compounds <Raw material solution preparation process> Lanthanum nitrate hexahydrate (La(NO3)3·6H2O, purity 99.9%, Kanto Chemical Co., Ltd.), strontium nitrate (Sr(NO3)2, purity 98.0%, Kanto Chemical Co., Ltd.), and nickel nitrate hexahydrate (Ni(NO3)2·6H2O, purity 98%, Kanto Chemical Co., Ltd.) were mixed in a ratio that would result in the stoichiometric composition of LaSrNiO4 to prepare a raw material solution consisting of a nitrate aqueous solution (0.03M). LaSrNiO4 has the general formula: Re 2-x Sr x MO 4±δIn this case, the rare earth metal (Re) is lanthanum (La), the metal element (M) is nickel (Ni), corresponding to the case where x = 1.0 and δ = 0.
[0054] <Freeze-drying process> 100 ml of the obtained raw material solution (aqueous nitrate solution) was placed in a Teflon (registered trademark) beaker. Next, liquid nitrogen was placed around the beaker to rapidly cool and freeze the raw material solution. The frozen solution was depressurized to 20 Pa and left for 3 days to dry without melting the solvent (water). As a result, a metal salt mixture composed of uniform dry powder was obtained.
[0055] <Firing process> The obtained metal salt mixture (dry powder) was placed in an alumina crucible and calcined in air at 700 - 1000 °C for 1 hour for thermal decomposition to obtain a mixed powder of oxide and carbonate. The obtained mixed powder (calcined powder) was pulverized using an agate mortar, placed in an alumina crucible again, and subjected to full firing in air at 1200 °C for 8 hours to obtain a product (compound). This product was a powder composed of complete oxide.
[0056] (2) Evaluation of the product Regarding the obtained product, evaluations of various properties were carried out as follows.
[0057] <X-ray diffraction> The crystal phase of the product was identified by the powder X-ray diffraction (XRD) method. The analysis conditions were as follows.
[0058] - X-ray diffractometer: X’Pert Pro MRD (manufactured by Spectris Co., Ltd.) - Radiation source: CuKα (Kβ filter: Ni film) - Tube voltage: 45 kV - Tube current: 40 mA - Scan speed: 5.6° / min - Scan range (2θ): 20 - 60°
[0059] <BET specific surface area> The BET specific surface area of the product was measured. The measurement was performed as follows. Using a fully automatic gas adsorption measurement device AS1-MP (manufactured by Quantachrome), the measurement was performed by the BET method using krypton gas as a gas adsorption method. After the sample was degassed in vacuum at 100°C for 5 hours, the specific surface area was measured at the temperature under liquid nitrogen.
[0060] <Structural Observation> The products were subjected to secondary electron image (SEM) observation using a scanning electron microscope (ULTRA55, manufactured by Carl Zeiss) and composition (Ni, Sr, and a) surface analysis using an energy dispersive X-ray spectrometry (EDS) device (Quan Tax, manufactured by BRUCKER) to evaluate the uniformity of the structure and composition.
[0061] <Oxidation-reduction activity> The oxygen reduction activity of the obtained product was evaluated by convection voltammetry using a rotating disk electrode (RDE). 2 The evaluation was carried out as follows.
[0062] Using the obtained product (powder), a catalyst ink was prepared by the following procedure. First, ion-exchanged water and 2-propanol were mixed in a ratio of 4:1 to prepare the ink solvent, and 5 mg of the synthesized product (powder), 0.16 mL of a 10 wt% Nafion solution (527114 manufactured by SIGMA-ALDRICH) and 21.3 mg of acetylene black (VLCAN XC72 manufactured by Cabot Corporation) were mixed with 5 mL of this solvent. The resulting mixture was ultrasonically dispersed for 30 minutes using a homogenizer while cooling the surroundings with water to prepare a catalyst ink. Next, 8.3 μL of this catalyst ink was dropped onto a glassy carbon electrode using a microsyringe, and dried using hot air to obtain a concentration of 0.042 mg / cm. 2The rotating disk electrode with the catalytic electrode film formed was attached to a potentiostat, and the electrode surface was placed facing downwards in contact with the water surface of a three-electrode cell filled with an alkaline aqueous solution. In this state, the electrochemical reaction was measured while the disk was rotating.
[0063] When a disk is rotated in water, the amount of aqueous solution flowing onto the electrode surface changes depending on the rotation speed. In general, three types of phenomena contribute to electrode reactions: (A) diffusion of reactants to the electrode surface, (B) charge transfer on the electrode surface, and (C) escape of products from the electrode surface. However, convective voltammetry can evaluate the effect of (B), which is due to the nature of the material, by observing the electrochemical reaction with the convective speed changed in the electrolyte.
[0064] The measurement was carried out as follows. An oxygen-saturated 1.0 M potassium hydroxide solution obtained by bubbling oxygen for 30 minutes was used as the electrolyte, and the catalytic electrode was placed in the solution. The measurement temperature was 25°C, the reference electrode was a reversible hydrogen electrode (RHE), and the counter electrode was a platinum wire. The potential scanning rate was set to 5 mVs using a potentiostat (Hokuto Denko HZ-5000). -1 The current value was measured while rotating the electrodes at a rotation speed of 1600 rpm.
[0065] (3) Results The X-ray diffraction pattern of the product (metal composite oxide) obtained in Example 1 is shown in Figure 1. In addition, Figure 1 also shows the diffraction lines of LaSrNiO4 (space group F4 / mmm), LaSrNiO4 (space group I4 / mmm), Sr(OH)2·H2O, SrCO3, and NiO recorded in the powder X-ray diffraction intensity database (Powder Diffraction File; PDF).
[0066] As shown in FIG. 1, only the diffraction lines of LaSrNiO4 (PDF#01-089-8315) of space group I4 / mmm were observed in the X-ray diffraction pattern, and the diffraction lines of SrCO3 (PDF#00-005-0418), Sr(OH)2·H2O (PDF#01-077-2336), and NiO (PDF#00-047-1049) were not observed. Therefore, it was found that in Example 1, a single phase of LaSrNiO4 of space group I4 / mmm could be synthesized. In addition, this product had a BET specific surface area of 0.43 m 2 / g, which is a large specific surface area that can exert a catalytic function.
[0067] Moreover, the SEM image of the product obtained in Example 1 and the results of surface analysis of the composition (Ni, Sr, La) are shown in Figure 2. It was confirmed that this product had a uniform structure and a uniform composition (Ni, Sr, La).
[0068] The evaluation results of the oxygen reduction activity of the product of Example 1 are shown in Figure 3. As shown in Figure 3, a linear sweep voltammogram (LSV) was obtained. This confirmed that the product exhibited oxygen reduction activity.
[0069] Comparative Example 1 (1) Preparation of compounds <Raw material solution preparation process> We attempted to synthesize LaSrNiO4 using the citrate complex method. First, lanthanum nitrate hexahydrate (La(NO3)3·6H2O, 99.9% purity, Kanto Chemical Co., Ltd.), strontium nitrate (Sr(NO3)2, 98.0% purity, Kanto Chemical Co., Ltd.), and nickel nitrate hexahydrate (Ni(NO3)2·6H2O, 98% purity, Kanto Chemical Co., Ltd.) were dissolved in ion-exchanged water in the ratio that would result in the stoichiometric composition of LaSrNiO4 to prepare a raw material solution consisting of an aqueous nitrate solution (0.02 M).
[0070] <Gelling process> The obtained raw material solution (nitrate solution) was mixed with a citric acid solution (0.02M) in an equimolar ratio of citric acid to metal ions to form a citric acid complex of metal ions. Next, the obtained citric acid complex was heated on a hot plate heated to 80°C to evaporate and remove the water solvent to form a gel. It was found that a white precipitate was observed in the green gel, impairing uniformity. When a gel was prepared from lanthanum nitrate hexahydrate and nickel nitrate hexahydrate in the same manner without using strontium nitrate, no white precipitate was formed and a green, uniform dried product was obtained. From this, it was found that in Comparative Example 1, strontium (Sr) ions did not form a citric acid complex, but formed a white precipitate consisting of a strontium compound.
[0071] <Firing process> The resulting heterogeneous gel was transferred to an alumina crucible and calcined in air at 350°C for 2 hours in an electric furnace to obtain a calcined powder. The calcined powder was then taken out into a mortar and crushed. The crushed calcined powder was pre-calcined in an electric furnace at 1000°C for 1 hour, and then calcined at 1200°C for 8 hours. The resulting product (calcined product) consisted of complete oxides.
[0072] (2) Evaluation of the product For the product obtained in Comparative Example 1, the crystal phase was identified by powder X-ray diffraction (XRD) in the same manner as in Example 1. In addition, SEM images were observed using a scanning electron microscope, and composition (Ni, Sr, La) surface analysis was performed using EDS.
[0073] (3) Results The X-ray diffraction pattern of the product obtained in Comparative Example 1 is shown in Figure 4. As shown in Figure 4, the product did not contain by-products such as SrCO3 (PDF#00-005-0418), Sr(OH)2·H2O (PDF#01-077-2336), and NiO (PDF#00-047-1049). However, two types of LaSrNiO4 with different symmetries (space group I4 / mmm (PDF#01-089-8315) and space group F4 / mmm (PDF#01-076-9307)) were synthesized in a mixed form.
[0074] The SEM image of the product obtained in Comparative Example 1 and the results of surface analysis of the composition (Ni, Sr, La) are shown in Figure 5. This product had non-uniform particle size and shape, and also had a non-uniform composition (Ni, Sr, La).
[0075] Examples 2 to 6 (1) Preparation of compounds In the raw material solution preparation process, the general formula: Re 2-x Sr x MO 4±δ In the above, products were produced in the same manner as in Example 1, except that x = 0.4 (Example 2), x = 0.6 (Example 3), x = 0.8 (Example 4), x = 1.2 (Example 5), or x = 1.4 (Example 6) was used instead of x = 1.0.
[0076] (2) Evaluation and Results For the products obtained in Examples 2 to 6, the crystal phase was identified by powder X-ray diffraction (XRD) in the same manner as in Example 1. As a result, it was confirmed that a single-phase compound was obtained. In addition, when the oxygen reduction activity was evaluated by convection voltalmetry using a rotating disk electrode in the same manner as in Example 1, a linear sweep voltammogram could be drawn, and it was confirmed that the oxygen reduction activity was exhibited.
[0077] Example 7 (1) Preparation of compounds The product was produced in the same manner as in Example 1, except that in the raw material solution preparation process, yttrium nitrate hexahydrate (Y(NO3)3·6H2O, purity 99.99%, Kanto Chemical Co., Ltd.) was used instead of lanthanum nitrate hexahydrate to attempt the synthesis of the YSrNiO4 compound.
[0078] (2) Evaluation and Results For the product obtained in Example 7, the crystal phase was identified by powder X-ray diffraction (XRD) in the same manner as in Example 1. As a result, it was confirmed that a single-phase compound was obtained. In addition, when the oxygen reduction activity was evaluated by convection voltalmetry using a rotating disk electrode in the same manner as in Example 1, a linear sweep voltammogram could be drawn, and it was confirmed that the product exhibited oxygen reduction activity.
[0079] Example 8 (1) Preparation of compounds The product was produced in the same manner as in Example 1, except that in the raw material solution preparation process, neodymium nitrate hexahydrate (Nd(NO3)3·6H2O, purity 99.95%, Kanto Chemical Co., Ltd.) was used instead of lanthanum nitrate hexahydrate to attempt the synthesis of the NdSrNiO4 compound.
[0080] (2) Evaluation and Results For the product obtained in Example 8, the crystal phase was identified by powder X-ray diffraction (XRD) in the same manner as in Example 1. As a result, it was confirmed that a single-phase compound was obtained. In addition, when the oxygen reduction activity was evaluated by convection voltalmetry using a rotating disk electrode in the same manner as in Example 1, a linear sweep voltammogram could be drawn, and it was confirmed that the product exhibited oxygen reduction activity.
[0081] Example 9 (1) Preparation of compounds The product was produced in the same manner as in Example 1, except that in the raw material solution preparation process, gadolinium nitrate hexahydrate (Gd(NO3)3·6H2O, purity 99.95%, Kanto Chemical Co., Ltd.) was used instead of lanthanum nitrate hexahydrate to attempt the synthesis of the GdSrNiO4 compound.
[0082] (2) Evaluation and Results For the product obtained in Example 9, the crystal phase was identified by powder X-ray diffraction (XRD) in the same manner as in Example 1. As a result, it was confirmed that a single-phase compound was obtained. In addition, when the oxygen reduction activity was evaluated by convection voltalmetry using a rotating disk electrode in the same manner as in Example 1, a linear sweep voltammogram could be drawn, and it was confirmed that the product exhibited oxygen reduction activity.
Claims
[Claim 1] A method for producing a metal composite oxide, which is a material for an oxygen reduction catalyst and has a crystal structure similar to perovskite and contains strontium (Sr) as an A-site element and a metal element (M) as a B-site element, comprising the steps of: preparing a raw material solution containing components of the metal composite oxide and a solvent; A step of freezing and solidifying the raw material solution, and sublimating and removing the solvent from the resulting solidified product while it is in a frozen state to obtain a metal salt mixture; and heating the metal salt mixture to form a metal composite oxide; Including, the metal composite oxide is a Rudolfden-Popper type compound containing strontium (Sr) and a rare earth metal (Re) as A-site elements and a metal element (M) as a B-site element; The metal composite oxide is represented by the general formula Re 2-x Sr x M.O. 4±δ (wherein 0.5≦x≦1.5, 0≦δ≦0.25), The rare earth metal (Re) is at least one selected from the group consisting of lanthanum (La), neodymium (Nd), gadolinium (Gd), and yttrium (Y); The metal element (M) is nickel (Ni), The metal composite oxide has a BET specific surface area of 0.4 m 2 / g or more of powder, The raw material solution contains components of a nitrate of strontium (Sr), a nitrate of a rare earth metal (Re), a nitrate of a metal element (M), and a solvent, The method, wherein the raw material solution does not contain organic substances such as oxycarboxylic acids and glycols.
Citation Information
Patent Citations
Nox sensor
JP1996005593A
Shape anisotropy ceramic powder and its production
JP1998114570A
Ruthenium compound oxide powder and method for manufacturing the same
JP2006298655A
Photocatalyst and method for reducing nitrate ion and nitrite ion
JP2009214033A
Titanate of perovskite or derived structure thereof, and use thereof
JP2009263225A